Āẏāta Ālī Khām̐ - Mujatabā, Ābula Kāśems Muhammada (Bāṃlādeśa saṅgīta sirija, 1979)
Biographical sketches of Āẏāta Ālī Khām̐, 1884-1967, Mohāmmada Hosena Khasaru, 1903-1959, and Kamala Dāśagupta, 1912-1974, Banglaḍeshi musicians.